PENERAPAN MODEL GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN SEJARAH MATERI PENGARUH SEJARAH DUNIA TERHADAP SEJARAH BANGSA INDONESIA ABAD 18-20 - -, Matroji (PEDAGOGIA, 2016)
This study aims to improve student learning outcomes in learning history. This research was conducted in classes IX IPS SMAN 1 Tambun Utara regency of Bekasi on January 20, 2015 until April 15, 2015 by using the Classroom Action Research. Data collection techniques through interviews, observation, achievement test, documentation, procedures: (a) planning of the action; (B) implementation of the action; (C) observation; and (d) reflection. The results showed that the implementation of cooperative learning model of Group Investigation (GI) on the material Effect Against World History History of the Nation Indonesia Ages 18-20, can improve student learning outcomes with a standard limit value of history is completed 70. Prior to the implementation of cooperative learning model of Group Investigation ( GI) average value hump students is 61.35, but after the implementation of cooperative learning model of Group Investigation (GI) average value grade students into 70.68 in the first cycle and 75 413 in the second cycle. A total of 31 students (83.78%) scored above 70 on the 75% of the planned target by the end of the second cycle. Besides the implementation of cooperative learning model Investigation Group can also improve learning outcomes of students of class XI IPS SMAN 1 Tambun Utara of categories less successful in the first cycle to the category managed in the second cycle.Â Keywords: Cooperative learning model group investigation , world history , history of Indonesia